A psychospiritual integration frame of reference for occupational therapy. Part 2: Transformative occupations and the change process - Chris Kang (SAGE Publishing, 2017)
This paper builds upon the first in the series on psychospiritual integration (PSI) and examines the concept of transformative occupations and the process of change underpinning occupational therapy from a PSI perspective. A repertoire of new terms highlighting finer distinctions in the concept of occupation will be introduced and explained, as will the dynamic for transformation inherent in the psychospiritual integration change process. Suggestions for PSI-informed occupational therapy practice will be explored.